MAKNA UPACARA BATIMBANG DALAM TRADISI MASYARAKAT SUKU BANJAR KUALA TUNGKAL, PROVINSI JAMBI - Jailani, M. Syahran; Nurhasanah, Nurhasanah (UIN Antasari, 2018)
This paper discusses an academic analysis of batimbang traditional ceremony which is one form of the human life cycle ceremony is conducted by urang Banjar Kuala Tungkal Jambi Province. This batimbang ceremony is only intended for baby (child) who born exactly the Safar month in the hijriyah month. Urang Banjar believing, baby (child) was born in the Safar month that is believed in the life ranging from baby to adult will be various experience calamities even some of the urang Banjar considers baby who born in the Safar month or bad month. Urang Banjar carry out this ceremony because they believe the Safar month as a bad month full of reinforcements and ways, and the misfortune of Safar month will befall the child’s life. Batimbang means weighting. Something is weighed to be balanced and sufficient. Therefore, in order to avoid inflicting misfortune and distress to the child, so the child must be weighed as a form of ritual refusing reinforcement and recovery from unlucky circumstances.